NAGA SEBAGAI SIMBOL PULAU BUTON - sanufi, sanufi (JURNAL ILMU BUDAYA, 2021)
Deciphering the symbols of an area we will talk a lot about the meaning contained in these symbols. There are many things that build meaning construction on a symbol that is used by an area. Both in terms of selection, as well as the background that makes a certain symbol chosen by an area to make it an icon. In connention with this, Dragon which are symbols of the Buton region certainly have different meanings than the symbols in other regions. Through semiotic analysis with the theory used by Ferdinand de Saussure, it can be studied that dragons which are symbols of the area of Buton are contextula language systems that clearly contain certain meanings. The elements that construct these symbols so that they are meaningful are certainly related to the sign system as a symbol. As a language system.